1997
DOI: 10.1074/jbc.272.31.19248
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of Platelet Cortactin by Calpain

Abstract: Cortactin, a substrate of pp60 c-src and a potent filamentous actin binding and cross-linking protein, is abundant in circulating platelets. After stimulation of platelet aggregation with collagen, cortactin undergoes a dramatic increase in tyrosine phosphorylation followed by a rapid degradation. The cleavage of platelet cortactin was detected in lysates prepared using either Triton-containing buffer or SDS-sample buffer. However, the degradation of cortactin was not observed in platelets derived from a Glanz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 29 publications
4
62
0
Order By: Relevance
“…In addition, calpain-induced cleavage of FAK may be linked to specific tyrosine phosphorylation of FAK that leads to complex dissociation, perhaps releasing FAK and permitting its cleavage by calpain. Previous studies demonstrate that Src-mediated tyrosine phosphorylation of cortactin and the NR2 subunits of NMDA receptors influences the ability of v-Src-dependent Calpain and Caspase Cleavage of FAKthese proteins to be cleaved by calpain (49,50). It is therefore tempting to speculate that v-Src-dependent phosphorylation of FAK may influence the suitability of FAK to act as a substrate for calpain.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, calpain-induced cleavage of FAK may be linked to specific tyrosine phosphorylation of FAK that leads to complex dissociation, perhaps releasing FAK and permitting its cleavage by calpain. Previous studies demonstrate that Src-mediated tyrosine phosphorylation of cortactin and the NR2 subunits of NMDA receptors influences the ability of v-Src-dependent Calpain and Caspase Cleavage of FAKthese proteins to be cleaved by calpain (49,50). It is therefore tempting to speculate that v-Src-dependent phosphorylation of FAK may influence the suitability of FAK to act as a substrate for calpain.…”
Section: Discussionmentioning
confidence: 96%
“…The biochemical role of calpain in MC adhesion is undoubtedly complex. Given that calpain can cleave a number of cytoskeletal-associated proteins, such as talin, cortactin paxillin, and the ␤ 1 integrin cytoplasmic tail (39,40,50), the enzyme may have a role in both focal contact formation and reorganization of the actin cytoskeleton. In T cells it has been demonstrated that calpain cleaves PTP-1B, causing the relocation of the 42-kDa form of the phosphatase from the endoplasmic reticulum to sites of focal contacts via association with p130 cas .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, actin cross-linking activity of cortactin and its calpain-mediated proteolysis are regulated by tyrosine phosphorylation (34,35). FAK is another major tyrosine kinase involved in cytoskeletal regulation (36).…”
Section: Discussionmentioning
confidence: 99%